1987
DOI: 10.2151/jmsj1965.65.6_949
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Clouds in Antarctica from Infrared Multispectral Data of AVHRR

Abstract: A method to detect cloud cover in the Antarctic using only the infrared channels of AVHRR is discussed. From the data of NOAA-7 received at Syowa Station, the difference in the brightness temperature of each channel appeared to be useful for the identification of clouds. The brightness temperature of the channels 3 (3.7*m) and 4 (11*m) shows the positive difference when the thickness of clouds are in some particular range, and then tends to show negative difference for the thick cloud. Thin clouds have the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 18 publications
2
63
0
4
Order By: Relevance
“…The main BTD advantage is its very simple and fast application, while the main drawbacks are the false alarms ("false positive" when a particular pixel is recognized as ash affected but that in fact doesn't contain ash and vice-versa for "false negative") obtained in specific and well documented cases (Simpson et al, 2000;, as over clear land surfaces at night (Platt and Prata, 1993), over soils with a high quartz content (e.g. deserts) (Barton and Takashima, 1986), over very cold surfaces (Potts and Ebert, 1996), over ice-covered surfaces (Yamanouchi et al, 1987) and in presence of high water vapour content Yu et al, 2002;Corradini et al, 2008a). This latter effect, that tends to attenuate and in some cases can completely cancel-out the BTD signal, has been corrected by applying a procedure developed by Corradini et al (2008a).…”
Section: Brightness Temperature Difference Proceduresmentioning
confidence: 99%
“…The main BTD advantage is its very simple and fast application, while the main drawbacks are the false alarms ("false positive" when a particular pixel is recognized as ash affected but that in fact doesn't contain ash and vice-versa for "false negative") obtained in specific and well documented cases (Simpson et al, 2000;, as over clear land surfaces at night (Platt and Prata, 1993), over soils with a high quartz content (e.g. deserts) (Barton and Takashima, 1986), over very cold surfaces (Potts and Ebert, 1996), over ice-covered surfaces (Yamanouchi et al, 1987) and in presence of high water vapour content Yu et al, 2002;Corradini et al, 2008a). This latter effect, that tends to attenuate and in some cases can completely cancel-out the BTD signal, has been corrected by applying a procedure developed by Corradini et al (2008a).…”
Section: Brightness Temperature Difference Proceduresmentioning
confidence: 99%
“…Directional emissivity spectra of snow cover at thermal infrared (TIR) wavelengths are essential properties for remote sensing of the earth's thermal properties, such as snow surface temperature [1][2][3][4][5], cloud discrimination from space [6,7], and for estimating Earth's long-wave radiation budget on the Greenland and Antarctic ice sheets by broadband radiometer such as the clouds and the Earth's radiant energy system (CeRES) [8]. The spectra may also be potentially utilized for sensing remote planets in astronomical applications [9].…”
Section: Introductionmentioning
confidence: 99%
“…Inoue [1985,1987] found that cirrus clouds can be identified over tropical oceans using the difference between AVHRR channels 4 and 5 brightness temperatures. BTDs were then used by Yamanouchi et al [1987] …”
Section: Introductionmentioning
confidence: 99%